The prospective COVID-19 vaccine: willingness to pay and perception of community members in Ibadan, Nigeria (2021)
Background: The introduction of the COVID-19 vaccine necessitates the assessment of individual perception regarding the vaccine. This study aimed to assess the perception of community members and willingness to pay for the prospective COVID-19 vaccine in Ibadan, Nigeria. Methods: A descriptive cross-sectional study design was used. Data were collected using an interviewer-administered questionnaire in September 2020. We studied community members aged 15 years and above using a multi-stage sampling technique. The perceptions of respondents about the COVID-19 vaccine were assessed on eight questions using the five-point Likert scale with a score point of “1” assigned for “Strongly Agree”, “2” for “Agree”, “3” for “Not decided”, “4” for “Disagree”, and “5” for “Strongly disagree”. During analysis, we reverse-coded the options by assigning a point of “1” for “Strongly disagree”, “2” for “Disagree”, “3” for “Not decided”, “4” for “Agree”, and “5” for “Strongly disagree”. However, questions asked in the negative directions were not reverse-coded during analysis. Eight questions were used to assess the perception of community members regarding the prospective COVID-19 vaccine, and overall, the maximum point was 40. Points greater than or equal to 32 points (80%) implied positive perception. Descriptive statistics were done. Chi-square tests were used for the assessment of associations between sociodemographic characteristics and willingness to pay for the prospective COVID-19 vaccine. We conducted logistic regression tests on statistically significant variables at p-values <0.05. Results: The mean age of the 440 respondents studied was 37.22 ± 15.36 years, 193 (49.00%) were males, and 292 (67.30%) of the respondents had heard of the prospective COVID-19 vaccine. Among them, 232 (79.50%) respondents had positive perception regarding COVID-19 vaccine. Individuals in the fifth wealth quintile were ten times more likely to be willing to pay for the prospective COVID-19 vaccine compared to those in the first wealth quintile (Adjusted Odds Ratio = 9.57, 95% CI [2.88–31.82], p = <0.01). Conclusion: The prospective COVID-19 vaccine should be subsidized or made freely available to everyone.